Design of A Multi-Speed Pneumatic Linear Transfer System - Didi Widya Utama; Jason Waworuntu; Agus Halim; Agustinus Purna Irawan; Robin Averil; Satrio Tauladan; Kevin Raynaldo (Fakultas Teknik Universitas Pancasila, 2025)
One of the fastest-growing industries in this modern era is automation, with the goal of enhancing efficiency, productivity, and precision. In this context, production system automation is key to achieving these goals. This research reviews the use of pneumatic linear transfer systems in modern manufacturing industries that are oriented toward efficiency, productivity, and flexibility. This research uses the VDI 2221 method in conjunction with structured design approaches and pneumatic technology to design and construct a multi-speed pneumatic linear transfer system. New developments in the pick-and-place system allow it to accelerate for picking up objects and decelerate for placing them utilizing a pneumatic system. With an emphasis on enhancing production process efficiency, productivity, and flexibility, it is hoped that this research will significantly contribute to developing automation technology in the manufacturing sector. The FEA analysis results also show that this multi-speed pneumatic linear transfer system tool can safely accommodate the applied load.